PELATIHAN DAN PENDAMPINGAN BAGI PELATIH SSB USIA DINI DALAM MELATIH AKURASI TENDANGAN MENGGUNAKAN ADIDAS SMART BALL - Pahala Tua Hutajulu; Octolia Togibasa (JURNAL PENGABDIAN PAPUA, 2019)
On this event, smart ball technology  were applied for kicking exercise in Papua United Football Club. Smart ball is a ball which equipped with sensor therefore the users can build an analysis dan make simulation of ball movement which related to improvement of the quality of exercise. From the testimony of participants, we can understand that this technology were effective, especially because the shape of ball is not different from common ball therefore there were no side effects when the players kicking the samrt ball. However the positive points were they can measure the speed, truning point, and ball speed in only 5 to 10 minutes when using smart ball. If the team ccould get those data in advance they can make an evaluation for players. We hope this new technology can help this football club to improve the uality of players. This technique also can be consider as one of the exercise method for football club in Jayapura.Keywords: smart ball technology, football, smart ball, Papua